Optimalisasi Pemanfaatan Media Sosial Pada Usaha Mikro Kecil Menengah (UMKM) Pada Produk Online Shopping Di Bengkayang - okta, oktaviani (Jurnal Ekonomi dan Bisnis, 2024)
In the current era of globalization, product marketing is not only done directly but can also be done indirectly, which is usually called offline marketing and online marketing. The sophistication of technology now makes it easier for business actors to run a business, but in general, whatever marketing is used by business actors to promote their products comes down to each marketing method that can provide profits. Offline Marketing is marketing that is carried out directly or Face to Face promotion, in this marketing it is easy to do but it only covers that scope and does not get a wide reach. With the Online Shop the reach in marketing will be wider and online promotion will make it easier for Fashion Selashop to promote products to consumers within and outside the scope. Online Shop is online marketing that uses the internet network which can be implemented through social media such as WhatsApp, Instagram and Facebook because these three social media are frequently or widely used by everyone. Fashion Selashop is an MSME which provides products online and is marketed online. Online Shop is a solution for business actors in developing their business because its easy marketing provides smoothness in marketing products to consumers far and near so that many people know about the products being sold. Online Shop products make it easy for consumers who prefer to shop from home because they don't have to come directly to the place, but just by looking at their cellphone, consumers can shop easily.Keywords: Fashion Selashop, Social Media, Online Shop